Factors of food label in influencing buying decision making among students at UiTM Cawangan Terengganu Kampus Dungun / Siti Nadiah Zakaria and Syahida Md Yusof - Zakaria, Siti Nadiah; Md Yusof, Syahida (2019)
In Malaysia, food label have been compulsory to be applied in all the food products in order to help consumer acknowledge and make proper decision before buy it by reading the information provided on it. This study expected to improve the understanding and concerning reading the food labeling among students at UiTM Cawangan Terengganu Kampus Dungun by looking at which the most factor leads to the buying decision. The questionnaires were distributed to the students at UiTM Cawangan Terengganu Kampus Dungun according to the number of respondents required for each faculty which calculated by using stratified sampling method. The objective of this study are to identify level of nutrition facts, ingredients, health claim, Halal logo and expiry date in influencing buying decision making and to identify the most common variable that influence buying decision making. Descriptive analyses and Multiple Regression are used in the study. The finding of this study showed the expiry date has highest value which influences students UiTM Dungun in buying decision making compare to other variables.